Islamic Religious Education as an Effort to Strengthen Religious Literacy among Adolescents - lutfi firdausi (Badan Usaha Milik Desa Berkaho Pungpungan, 2025)
This study aims to examine the role of Islamic Religious Education (PAI) as an effort to strengthen religious literacy among adolescents in the contemporary era. Adolescents today face rapid globalization, digital transformation, and cultural shifts that influence their understanding and practice of religion. These conditions create both opportunities and challenges for PAI in nurturing balanced personal development that integrates knowledge, faith, and moral values. Using a systematic literature review (SLR) approach, this research analyzed relevant studies published from 2018 to 2024 focusing on strategies, methods, and innovations in enhancing religious literacy among youth. The findings reveal that PAI contributes significantly to improving adolescents’ cognitive understanding of religion while also fostering ethical awareness and spiritual resilience. Innovative strategies such as contextual learning, digital-based approaches, and value-oriented pedagogy were identified as effective in strengthening religious literacy. Nevertheless, the effectiveness of these efforts depends on several factors, including teachers’ digital competencies, institutional support, and active engagement of students in meaningful learning activities. The novelty of this study lies in highlighting the importance of integrating PAI with technological advancement and character-building approaches to ensure its relevance in the digital era. This research concludes that strengthening religious literacy through PAI must be carried out holistically by combining knowledge, practice, and values to prepare adolescents as morally responsible individuals capable of making positive contributions to society.